Macroscopic heat release in a molecular solar thermal energy storage system. Issue 1 (4th September 2018) - Wang, Zhihang; Roffey, Anna; Losantos, Raul; Lennartson, Anders; Jevric, Martyn; Petersen, Anne U.; Quant, Maria; Dreos, Ambra; Wen, Xin; Sampedro, Diego; Börjesson, Karl; Moth-Poulsen, Kasper
Abstract : The development of solar energy can potentially meet the growing requirements for a global energy system beyond fossil fuels, but necessitates new scalable technologies for solar energy storage. Abstract : The development of solar energy can potentially meet the growing requirements for a global energy system beyond fossil fuels, but necessitates new scalable technologies for solar energy storage. One approach is the development of energy storage systems based on molecular photoswitches, so-called molecular solar thermal energy storage (MOST). Here we present a novel norbornadiene derivative for this purpose, with a good solar spectral match, high robustness and an energy density of 0.4 MJ kg −1 . By the use of heterogeneous catalyst cobalt phthalocyanine on a carbon support, we demonstrate a record high macroscopic heat release in a flow system using a fixed bed catalytic reactor, leading to a temperature increase of up to 63.4 °C (83.2 °C measured temperature). Successful outdoor testing shows proof of concept and illustrates that future implementation is feasible. The mechanism of the catalytic back reaction is modelled using density functional theory (DFT) calculations rationalizing the experimental observations.